2017
DOI: 10.1080/0886022x.2017.1291433
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the appropriate fixation site to avoid peritoneal catheter migration based on a mechanical analysis

Abstract: Aim: To conduct mechanical analysis on the relationship between abdominal wall fixation point and the displacement of catheter top, and establish the finite element model for the complex forces and conditions that the catheter wears in human abdominal cavity, in order to provide the scientific basis for optimizing the catheter position in abdominal wall fixation method.Methods: Using the PIPE59 finite elements to divide units, and taking the lower part of catheter, that is, below interior polyester cuff to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Occasionally, large extent shift of the catheter tip under certain forces may result in catheter migration. Through the computational simulation and mechanical analysis, we had ascertained the necessity of additional catheter fixation and also identified the appropriate fixation site . Actually, a large body of evidence from others has emphasized the need for additional catheter fixation to avoid migration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, large extent shift of the catheter tip under certain forces may result in catheter migration. Through the computational simulation and mechanical analysis, we had ascertained the necessity of additional catheter fixation and also identified the appropriate fixation site . Actually, a large body of evidence from others has emphasized the need for additional catheter fixation to avoid migration .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, additional catheter fixation has been emphasized by us and others in preventing catheter migration (17)(18)(19)(20)(21)(22)(23). We had further analyzed the mechanical mechanism of why and where to fix the catheter (24). We also developed a novel maneuver of catheter fixation in the assistance of an apparatus termed "Wang's forceps," which has been implemented in the approach of open surgical catheter insertion or displaced catheter reposition (23,25).…”
mentioning
confidence: 99%
“…The study found that the site 9 cm from the interior catheter cuff had the least risk of migration rate and intraperitoneal complication. 3 In addition, in the present case, the free-moving greater omentum at the right side of abdomen was also suture-fixed to the right upper quadrant to help expose the small intestinal mesentery and prevent the potential wrapping of the tip of the PD catheter by the greater omentum. The greater omentalpexy technique was described in the literature.…”
mentioning
confidence: 96%